The Impacts of Training and Eye - Hand Coordination toward Smash Outcome of Volleyball Extracurricular Members (Journal of Physical Education and Sports, 2019)
The purpose of this research is to find out and analyse: the different impancts of Plyometric Split Squat Jump and Jump to box trainings toward smash outcome of volleyball extracurricular members in Public Senior High School 01 Soe, Southern Middle Timor Regency. The different impacts of high and low eye-hand coordination toward smash outcomes of the members. This research uses experimental method using factorial 2x2 design. The technique of analysing the data uses Analysis of Variant (ANOVA) on level of significance (Î±) 0.05. The independent variables are Plyometric Split Squat Jump and Jump to box. High and low eye-coordination are the attributes of the variables and the variables are related to smash outcomes. The findings of the research are: there is significant different impacts between those trainings methods toward the outcome with significant score (0.032) < Î± (0.05) and the score of Fvalue (6.036) > Ftable (3.35), There is significant difference between high and low eye-hand coordination toward the outcome in which the significant score is (0.042), < Î± (0.05) and Fvalue (4.696) > Ftable (3.35), There is an interaction among training methods and the coordinations toward the outcome with significant score (0.034) < Î± (0.05) and Fvalue (7.234) > Ftable (3.35). The conclusions of this research are: there is significant difference between the training methods toward the outcomes; there is significant different between the coordinations toward the outcomes; and there is an interaction among the training methods and the coordinations toward the outcomes.